COMPARATIVE PUBLIC ADMINISTRATION: THE ESSENTIAL READINGS - Lawrence R. Jones (JAI Press is an imprint of Elsevier, 2006)
Comparative public administration is a branch of public administration that focuses on comparative analysis of administrative processes and institutions. The comparative approach has been around since the inception of government. As a specialized field of interest, the significance of comparison cannot be accurately traced to a single event or country. What we know is that early scholarly work in the parent field drew upon knowledge and perspectives with cross-national origins. For example, Ferrel Heady reminds us that pioneers in the study of American public administration, including Woodrow Wilson and Frank Goodnow, made full use of lens’ provided in European scholarship (Heady, 2001, p. 6). Likewise, past and recent nonwestern scholarship has drawn substantial inspiration from European and American models. The reasons for this are easy to discern. At least three can be advanced. First is the colonial experience – with most countries in the southern hemisphere having derived a large part of their bureaucratic structures from their former colonizers, the importance of comparative approaches cannot be overemphasized. Second is the increased flow of information worldwide has made it easier for scholars to compare notes on administrative systems in different countries. Third are domino effects of human development, including deliberate attempts by various international bodies to encourage development via adoption of institutional and administrative models that have proven to enhance the quality of life. In fact, coincidentally, sustained comparative analysis in public administration occurred at the end of the World War II when many organizations with a global outreach emerged.